Clinical prediction of bacteremia and early antibiotics therapy in patients with solid tumors. (28th September 2022) - Hyak, Jonathan M.; Al Mohajer, Mayar; Musher, Daniel M.; Musher, Benjamin L.
Abstract: Objective: To investigate the relationship between the systemic inflammatory response syndrome (SIRS), early antibiotic use, and bacteremia in solid-tumor patients. Design, setting, and participants: We conducted a retrospective observational study of adults with solid tumors admitted to a tertiary-care hospital through the emergency department over a 2-year period. Patients with neutropenic fever, organ transplant, trauma, or cardiopulmonary arrest were excluded. Methods: Rates of SIRS, bacteremia, and early antibiotics (initiation within 8 hours of presentation) were compared using the χ 2 and Student t tests. Binomial regression and receiver operator curves were analyzed to assess predictors of bacteremia and early antibiotics. Results: Early antibiotics were administered in 507 (37%) of 1, 344 SIRS-positive cases and 492 (22%) of 2, 236 SIRS-negative cases ( P < .0001). Of SIRS-positive cases, 70% had blood cultures drawn within 48 hours and 19% were positive; among SIRS negative cases, 35% had cultures and 13% were positive (19% vs 13%; P = .003). Bacteremic cases were more often SIRS positive than nonbacteremic cases (60% vs 50%; P =.003), but they received early antibiotics at similar rates (50% vs 49%, P = .72). Three SIRS components predicted early antibiotics: temperature (OR, 1.7; 95% CI, 1.31–2.29; P = .0001), tachycardia (OR, 1.4; 95% CI, 1.10–1.69; P < .0001), and white blood-cell count (OR, 1.8; 95% CI, 1.56–2.14; P < .0001). Only temperature (OR, 1.6; 95% CI, 1.09–2.41; P = .01) and tachycardia (OR, 1.5; 95% CI, 1.09–2.06; P = .01) predicted bacteremia. SIRS criteria as a composite were poorly predictive of bacteremia (AUC, 0.57). Conclusions: SIRS criteria are frequently used to determine the need for early antibiotics, but they are poor predictors of bacteremia in solid-tumor patients. More reliable models are needed to guide judicious use of antibiotics in this population.